(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
Ferulic acid is a phenolic acid widely distributed in the plant kingdom. It presents a wide range of potential therapeutic effects useful in the treatments of cancer, diabetes, lung and cardiovascular diseases, as well as hepatic, neuro and photoprotective effects and antimicrobial and anti-inflammatory activities. Overall, the pharmaceutical potential of ferulic acid can be attributed to its ability to scavenge free radicals. However, recent studies have revealed that ferulic acid presents pharmacological properties beyond those related to its antioxidant activity, such as the ability to competitively inhibit HMG-CoA reductase and activate glucokinase, contributing to reduce hypercholesterolemia and hyperglycemia, respectively. The present review addresses ferulic acid dietary sources, the pharmacokinetic profile, antioxidant action mechanisms and therapeutic effects in the treatment and prevention of various diseases, in order to provide a basis for understanding its mechanisms of action as well as its pharmaceutical potential.